Glial cells improve Parkinson’s disease by modulating neuronal function and regulating neuronal ferroptosis - Li, Mengzhu; Chen, Mengxuan; Li, Haiyan; Gao, Da; Zhao, Lijun; Zhu, Meiling (Frontiers in Cell and Developmental Biology, 2025)
The main characteristics of Parkinson’s disease (PD) are the loss of dopaminergic (DA) neurons and abnormal aggregation of cytosolic proteins. However, the exact pathogenesis of PD remains unclear, with ferroptosis emerging as one of the key factors driven by iron accumulation and lipid peroxidation. Glial cells, including microglia, astrocytes, and oligodendrocytes, serve as supportive cells in the central nervous system (CNS), but their abnormal activation can lead to DA neuron death and ferroptosis. This paper explores the interactions between glial cells and DA neurons, reviews the changes in glial cells during the pathological process of PD, and reports on how glial cells regulate ferroptosis in PD through iron homeostasis and lipid peroxidation. This opens up a new pathway for basic research and therapeutic strategies in Parkinson’s disease.